2016
DOI: 10.1186/s12862-016-0630-3
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses to a climate regime change by sympatric, ice-dependent predators

Abstract: BackgroundModels that predict changes in the abundance and distribution of fauna under future climate change scenarios often assume that ecological niche and habitat availability are the major determinants of species’ responses to climate change. However, individual species may have very different capacities to adapt to environmental change, as determined by intrinsic factors such as their dispersal ability, genetic diversity, generation time and rate of evolution. These intrinsic factors are usually excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 72 publications
0
26
0
1
Order By: Relevance
“…Our model ignored the dispersal processes because the Pointe Géologie colony of emperor penguin is the colony where some marking was done for demographic studies and no observation of marked animals was made in neighboring colonies situated at 200 km for the nearest one. Recent genetic studies also suggested dispersal occurs but at low annual rates (≈0.15–0.17% per year; Cristofari et al ., ; Younger et al ., ). Here, we first describe the likelihoods for the three datasets shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Our model ignored the dispersal processes because the Pointe Géologie colony of emperor penguin is the colony where some marking was done for demographic studies and no observation of marked animals was made in neighboring colonies situated at 200 km for the nearest one. Recent genetic studies also suggested dispersal occurs but at low annual rates (≈0.15–0.17% per year; Cristofari et al ., ; Younger et al ., ). Here, we first describe the likelihoods for the three datasets shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
“…A coalescent study of East Antarctic Weddell seals indicated that the effective population size in this region has been stable since 80 kya (Younger, ). Over this period there were several major changes in climatic regime, including the LGM (Fig.…”
Section: Antarctic Sea Ice Breedersmentioning
confidence: 97%
“…Details of the tissue samples collected from emperor penguins at Halley Bay, Fold Island, Auster, Amanda Bay and Pointe Géologie can be found in Ref. (Younger, van den Hoff, Wienecke, Hindell, & Miller, 2016;Younger, Clucas, et al, 2015). All other samples were blood samples.…”
Section: Sampling and Sequencingmentioning
confidence: 99%
“…Emperor penguins have a relatively continuous distribution around Antarctica with most colonies being situated within the range of individuals foraging from adjacent colonies (Fretwell et al, 2012) ( Figure 1b). Their fast-ice breeding habitat is highly ephemeral, leading to changes in colony locations over years (Fretwell, Trathan, Wienecke, & Kooyman, 2014;LaRue et al, 2015;Trathan, Fretwell, & Stonehouse, 2011) and millennia (Younger, Clucas, et al, 2015;Younger et al, 2016). The low levels of genetic differentiation among emperor colonies likely reflect the need for flexibility in breeding location.…”
Section: Breeding Habitat Quality Continuity and Ephemeralitymentioning
confidence: 99%